2020
DOI: 10.1002/ese3.785
|View full text |Cite
|
Sign up to set email alerts
|

Study on crack propagation of the CO2 presplitting blasting empty hole effect in coal seam

Abstract: More than 95% of the coal seams mined in high gas, and outburst mines belong to low-permeability coal seams in China, and the difficulty of extracting coal seam gas has become a coal seam feature of most coal mines. 1 To improve the gas drainage efficiency and increase the permeability of coal seams, researchers at home and abroad have conducted much research on appropriate technologies for studying these parameters and have achieves some useful results, such as the use of a regional predrilling pump, 2,3 hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…However, the high-pressure gas blasting technology as a measure to increase the permeability of low-permeability coal seams is still in the development stage, and the related theoretical research is not perfect. Domestic and foreign scholars have carried out a large number of studies on the anti-reflection field of high-pressure gas in unconventional gas low-permeability reservoirs using theoretical analysis, physical experiment, and numerical simulations. It is found that the amount of high-pressure gas, impact mode, and in situ stress have a great influence on the crack initiation mode and crack propagation law of coal. Some scholars detected the macroscopic mechanical properties and microstructure changes of coal and rock mass before and after high-pressure gas blasting by uniaxial/triaxial loading, acoustic emission detection, scanning electron microscopy (SEM), and mercury intrusion porosimetry (MIP) to reveal the cracking mechanism under a high-pressure gas impact.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high-pressure gas blasting technology as a measure to increase the permeability of low-permeability coal seams is still in the development stage, and the related theoretical research is not perfect. Domestic and foreign scholars have carried out a large number of studies on the anti-reflection field of high-pressure gas in unconventional gas low-permeability reservoirs using theoretical analysis, physical experiment, and numerical simulations. It is found that the amount of high-pressure gas, impact mode, and in situ stress have a great influence on the crack initiation mode and crack propagation law of coal. Some scholars detected the macroscopic mechanical properties and microstructure changes of coal and rock mass before and after high-pressure gas blasting by uniaxial/triaxial loading, acoustic emission detection, scanning electron microscopy (SEM), and mercury intrusion porosimetry (MIP) to reveal the cracking mechanism under a high-pressure gas impact.…”
Section: Introductionmentioning
confidence: 99%
“…Coal bodies around boreholes are affected by different moisture contents and exhibit distinct force characteristics. The crack sprouting, expansion and development processes in each stage are more complex and difficult to observe and characterize, especially regarding their influences on borehole sealing technology and the extraction effect [1][2][3][4][5]. Therefore, it is of great engineering significance to perform research on the image grayscale characteristics of coal bodies around boreholes with different moisture contents.…”
Section: Introductionmentioning
confidence: 99%
“…When the moisture content increases, the peak grayness corresponding to the peak stress point significantly decrease; the peak grayness of the moisture-bearing specimen rapidly increases, the grayness distribution rapidly changes to "high and narrow", the third-order moment µ arc increases, and the internal strain field is not uniformly distributed. These phenomena occur because the moisture-bearing specimens have a certain energy storage period before the stable crack extension stage when energy is released, stress concentration zones appear, and microscopic cracks are formed[25] 3. After the stress is loaded to σ f , the peak grayness of the dry specimen more rapidly decreases, the grayness distribution shifts to "low and narrow", the third-order moment µ arc decreases, and the grayness distribution remains in the(40,110) interval.…”
mentioning
confidence: 99%
“…In summary, most of the LCPTB research focuses on phase-transition mechanism [22,26,31], rock blasting [32,35], blasting antireflection [2][3][4]7,20,21] and blasting fracture propagation [11,20,36,37]. However, there is a lack of research on the initiation of the fracturing pipe and especially research on the relationship among controllable blasting parameters, blasting pressure and blasting effect in the LCPTB.…”
Section: Introductionmentioning
confidence: 99%